DO FOREIGN FUNDS AFFECT INDONESIAN CAPITAL MARKET LIQUIDITY? - said kelana asnawi (Universitas Lancang Kuning, 2021)
Trading Volume (Liquidity) is the perfect complement to returns. Therefore, research regarding volume becomes an important thing in the capital market. Various factors that influence the Liquidity (TV) are bid-ask spread; interest rates, exchange rates, and foreign funds. The study uses Amihud Illiquidity Ratio (AIR) as a proxy for liquidity. The data is the Indonesian Composite Index for liquidity, and all variables, daily basis; 2016-2019 period, divided into odd and even semester, with the linear regression model. The results showed that the bid-ask spread decreases trading volume, exchange rate and interest rates had a positive effect on AIR, where the greater the depreciation and the higher the interest rates, the lower the liquidity. For 2019, the foreign fund has a negative coefficient, which shows foreign funds increase capital market liquidity. In 2019, there will be a strengthening effect between foreign funds and the exchange rate Keyword: liquidity; trading volume; Amihud Illiquidity Ratio; bid-ask spread; exchange rate.